Study of the Pedestrian Mobility in an Urban Center: A Case in Costa Rica - Fernández-Garza, Ana; Hernández-Vega, Henry (Revista Geográfica de América Central., 2018)
We analyzed the pedestrian mobility in the urban center of the district of Guadalupe, in Goicoechea, San José, Costa Rica. The analysis includes the characterization of users and their flows, the pedestrian volume, and the levels of pedestrian service in the sidewalks studied. Pedestrian volumes were obtained through automatic counters; as well, manual counts were performed to evaluate the performance of the equipment used. A survey was conducted to characterize users and their trips and to know the perception about the pedestrian infrastructure. The study showed that the pedestrian population is very diverse, even so behaviors can be observed such as the decrease in the number of pedestrians as the age of the population interviewed increases after 55 years old. Pedestrians usually walk in the study area between five and 35 minutes (short distances); 79 % of the trips are intermodal, being the bus the main mode of transportation associated with pedestrian mobility in the sector. The Daily-Weekly Traffic Average (TPDS) for the study area is between 170 and 6517 pedestrians per day. The sidewalks allow the flow of pedestrians who walk through, obtaining a proper level of pedestrian service according to the capacity analysis performed.